2021
DOI: 10.1186/s12985-021-01727-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the intestinal microbial community altered during rotavirus infection in suckling mice

Abstract: Background Rotavirus (RV) is a principal cause of diarrhea. However, there is a limited understanding regarding alteration of the gut microbial community structure and abundance during RV infection. This study was to characterize any potential associations between RV infection and the intestinal microbiota. Methods Suckling mice were divided into normal group (NC) and infected group (RV) randomly. All of the suckling mice were euthanized four days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
2
5
2
Order By: Relevance
“…In a previous study, Chao 1 indices and Shannon indices were significantly reduced in the feces of diarrheal calves with BRV infection, while Simpson indices were significantly increased (Jang et al, 2019). Similarly, significant reductions in the α diversity of gut microbiota have been observed in human infants and other studied species (Engevik et al, 2020;Xiong et al, 2021;Zhao et al, 2021). There are some agreements or contradictions between our results and previous studies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In a previous study, Chao 1 indices and Shannon indices were significantly reduced in the feces of diarrheal calves with BRV infection, while Simpson indices were significantly increased (Jang et al, 2019). Similarly, significant reductions in the α diversity of gut microbiota have been observed in human infants and other studied species (Engevik et al, 2020;Xiong et al, 2021;Zhao et al, 2021). There are some agreements or contradictions between our results and previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…There are some agreements or contradictions between our results and previous studies. Only Chao 1 indices significantly increased in the fecal microbiota of human infants infected with rotavirus, while no significant difference is observed in all alpha diversity indices of the fecal microbiota of suckling mice with rotavirus-associated diarrhea (Xiong et al, 2021;Zhao et al, 2021). An explanation for these differences would be that changes in the gut microbiota of newborn animals are influenced by a variety of factors, including environment, diet, age, gender, and the type and virulence of viruses infected (Castro et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…The proportion of Bacteroides and Parabacteroides was increased, while the proportion of Firmicutes and Euryarchaeota was decreased when compared to healthy group. Interestingly, several studies based on RV-caused diarrhea in infants or neonatal mice observed a decrease in the abundance of Bacteroides [ 22 , 25 ], which is contradict with our finding. Since gut microbiota in 5-year-old children has not reached adult complexity yet [ 26 ], perhaps it exerts its impact on RV replication in a different way with adults.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, a significant reduction in gut microbial abundance and diversity was observed in diarrheic Père David’s deer ( Figure 1 ). Similar data were reported in diarrheic humans ( Homo sapiens ) [ 32 ], mice ( Mus musculus ) [ 33 ], Baer’s pochards ( Aythya baeri ) [ 23 ], musk deer ( Moschus berezovskii ) [ 19 ], and giraffes ( Giraffa camelopardalis reticulata ) [ 24 ]. Thus, gut microbiota diversity reductions may be typical features in diarrheic individuals, no matter the diarrhea type or causative species.…”
Section: Discussionsupporting
confidence: 75%